Comparing the psychological benefits that Chinese and Western classical music preferences bring to cognitive emotion regulation, self-esteem, and psychological resilience - Xin Shan; Xin Shan; Yuchen Wang; Long Luo (Frontiers in Psychology)
IntroductionThis study investigates the effects of preferences for Chinese and Western classical music on three key psychological constructs in adults: cognitive emotion regulation, self-esteem, and psychological resilience. Guided by the World Health Organization’s principles of mental health, the research aims to explore how preferences for these distinct musical traditions relate to individual psychological well-being.MethodsThe study analyzed data from 604 valid responses collected through questionnaires, supplemented by behavioral observations, to examine the impact of classical music preferences on the targeted psychological outcomes.ResultsFindings indicate that a preference for classical music (both Chinese and Western) significantly enhances cognitive emotion regulation, self-esteem, and psychological resilience, with the strongest effect observed on psychological resilience. Among moderating factors, age and educational attainment significantly influenced the relationship between music preference and the three psychological aspects, whereas gender had no significant moderating effect. Additionally, preference for Western classical music was found to be more effective than preference for Chinese classical music across all three dimensions, potentially attributed to its complex harmonic structure and rich emotional expression.DiscussionThese results provide empirical evidence for the link between classical music preference and psychological well-being, offering new insights for the development of music therapy strategies and mental health interventions.